Fiscalidad de las entidades religiosas en el Perú - Gildemeister Ruiz Huidobro, Alfredo (2019)
What is the main purpose of giving tax-exemptions to religious bodies on a secular state such as the Peruvian? Which principles or laws cover this treatment? Should it remain in force?. The author elaborates on these issues from their relation with the constitutional principles of religious freedom and equality as well as considers the tax treatment granted in Peru to religious entities from a historical perspective. Moreover, throughout this article, the author emphasizes on the role and legal treatment granted to the Catholic church from Canon Law and the Peruvian legal framework.